An improved version of Rivaie-Mohd-Ismail-Leong conjugate gradient method with application in image restoration - Nurul Akmal binti Mohamed (Tanjung Malim, 2023)
An improved version of Rivaie-Mohd-Ismail-Leong conjugate gradient method with application in image restoration by Nurul Akmal binti Mohamed